2018
DOI: 10.1002/bies.201700219
|View full text |Cite
|
Sign up to set email alerts
|

A Link Between Alzheimer's and Type II Diabetes Mellitus? Ca+2‐Mediated Signal Control and Protein Localization

Abstract: We propose protein localization dependent signal activation (PLDSA) as a model to describe pre-existing protein partitioning between the cytosol, and membrane surface, as a means to modulate signal activation, specificity, and robustness. We apply PLDSA to explain possible molecular links between type II diabetes mellitus (T2DM) and Alzheimer's disease (AD) by describing Ca -mediated interactions between the Src non-receptor tyrosine kinase and p52Shc adaptor protein. We suggest that these interactions may ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 74 publications
(138 reference statements)
0
3
0
Order By: Relevance
“…Nowadays, there are at least 1 billion people that are diagnosed with deficiency of VD around the world in the 21st century, and the trend is increasing by year [20]. More studies support the point that VD not only keeps the health of the skeleton through promoting the absorption of calcium [21] but also has important functions except nutritional effects, including regulating the immune system to exert anti-infective effects and improving the developmental process of noninfectious diseases [22,23]. The antioxidant function of vitamin C has been widely reported; however, the antioxidant effects and possible mechanism of VitD 3 have few studies.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, there are at least 1 billion people that are diagnosed with deficiency of VD around the world in the 21st century, and the trend is increasing by year [20]. More studies support the point that VD not only keeps the health of the skeleton through promoting the absorption of calcium [21] but also has important functions except nutritional effects, including regulating the immune system to exert anti-infective effects and improving the developmental process of noninfectious diseases [22,23]. The antioxidant function of vitamin C has been widely reported; however, the antioxidant effects and possible mechanism of VitD 3 have few studies.…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that PSMD9 inhibited tumor necrosis factor α (TNF-α)-mediated NF-kB activation via inhibition of nuclear factor kBα (IkBα) proteasome degradation (Hao et al, 2015). TNF-α is one determinant of AD and T2DM onset and progression (Tsutsui and Hays, 2018). In addition, the proteasome-mediated proteolysis plays a recognized role in neuronal development, synaptic plasticity, and protein quality control (Hao et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of BioEssays, Tsutsui and Hays propose another mechanism that can explain the association between T2DM and AD. The authors propose the hypothesis that increased intracellular Ca 2+ accumulation in diseased cells leads to altered signaling by changing the localization and protein‐protein interactions of key signaling mediators and scaffolding proteins.…”
mentioning
confidence: 99%